Health and Quality of Life Outcomes Among Patients Undergoing Surgery for End-Stage Ankle Arthritis. (October 2019) - Rajapakshe, Shanika; Sutherland, Jason M.; Wing, Kevin; Crump, Trafford; Liu, Guiping; Penner, Murray; Younger, Alastair; Veljkovic, Andrea; Redfern, Kate
Background: There is little research investigating which aspects of health-related quality of life change following ankle arthrodesis and total ankle replacement surgery. The objective of this study was to report on statistically and clinically relevant changes in multiple dimensions of health-related quality of life among patients undergoing ankle replacement or fusion surgery. Methods: This study was based on a prospective sample of ankle arthrodesis and total ankle replacement patients. Participants complete the Ankle Osteoarthritis Scale, EuroQoL's EQ-5D-3L, the Patient Health Questionnaire–9, and the pain intensity, interference with enjoyment of life, and general activity pain instrument. Instruments were completed preoperatively and postoperatively. Multivariate regression models were used to measure the change in health-related quality of life outcomes, adjusting for demographic, clinical, and health service utilization. Results: Participants achieved statistically significant improvements in health-related quality of life in each domain of measurement. The majority of participants reported clinically significant improvement in pain. Mild depressive symptoms were common, and clinically significant improvement in depression symptoms occurred in 22% of patients. Gains in health were more pronounced among participants reporting the worst preoperative health in all domains quality of life measured. Conclusions: Pain showed a clinically important improvement among 64% of participants whereas 22% reported a clinically meaningful improvement in their depression symptoms postoperatively. Clinically significant gains in health-related quality of life were not experienced by all participants in all dimensions. Further research is warranted to better understand the failure of some patients to improve in dimensions of health studied. Level of Evidence: Level III, comparative study.